1992
DOI: 10.1084/jem.176.6.1637
|View full text |Cite
|
Sign up to set email alerts
|

Antigen binding and idiotype analysis of antibodies obtained after electroporation of heavy and light chain genes encoding phosphocholine-specific antibodies: a model for T15-idiotype dominance.

Abstract: SununaryAntibodies bearing the T15 idiotype dominate the murine primary immune response to phosphocholine (PC). Analysis of antigen binding of antibodies derived from VI:DFL16.1:J.1 (V.1) germline and N region-derived variant heavy (H) chains and g22, K24, and K8 light (L) chains demonstrates that the T15H:K22L (T15) antibody binds PC at least 20-40 times better than other antibodies derived from alternate germline forms of the V.1 H chain and g22, K24, or K8 L chains. To achieve af~nities in the same range as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Both rearranged V H 1-DFL16.1-JH1 genes as well as rearranged V 22-J 5 genes were readily amplified from microdissected single germinal centers before the repertoire shift in serum Ab. Although we have not formally demonstrated the presence of T15 V H and V L genes within a single cell, the V 22-J 5 L chains form functional PC binding sites only when paired with the T15 H chain (41). Taken together, the amplification of canonical T15 H and L rearrangements within cells of the same germinal centers supports our immunohistochemical identification of T15 Id ϩ cells.…”
Section: Discussionsupporting
confidence: 65%
“…Both rearranged V H 1-DFL16.1-JH1 genes as well as rearranged V 22-J 5 genes were readily amplified from microdissected single germinal centers before the repertoire shift in serum Ab. Although we have not formally demonstrated the presence of T15 V H and V L genes within a single cell, the V 22-J 5 L chains form functional PC binding sites only when paired with the T15 H chain (41). Taken together, the amplification of canonical T15 H and L rearrangements within cells of the same germinal centers supports our immunohistochemical identification of T15 Id ϩ cells.…”
Section: Discussionsupporting
confidence: 65%
“…B1 antibodies are part of the repertoire of IgM synthesized prior to microbial exposure and have lower affinity than antibodies induced following infection (96). The major idiotype of anti-ChoP antibodies is T15, originally identified in mice (97,98). While ChoP modification of host molecules, including the major cell membrane lipid phosphatidylcholine, is very common, it has been shown that T15 antibodies do not recognize the ChoP epitope in intact human membrane lipids (99,100).…”
Section: Host Responses To Chopmentioning
confidence: 99%
“…Each V1 variant expresses a different V:D junction and pairs with a different light (L) chain to form a PC-binding Ab. The germ line T15 V1 H chain (95H-Asp) associates with 22 L chain, the M603 variant (95H-Asn) associates with 8 L chain, the M167͞ M511 variants (96H-Ala) associate with the 24 L chain, and the D16 variant (95H-Gly) associates with the 1c L chain (13,14). These V H 1-id ϩ Abs, with the exception of the D16-like variants, are generally highly protective against SPn in passive transfer assays (6,12).…”
Section: P Hosphocholine (Pc) Is the Immunodominant Epitope Foundmentioning
confidence: 99%